Midterm Outcomes and Surgical Approaches for Osteochondral Lesions of the Talus - Biehl, Christoph; Fritzsche, Carina; Walter, Nike; Biehl, Lotta; El Khassawna, Thaqif; Heiss, Christian; Rupp, Markus; Justus Liebig University Giessen (My University, 2025)
Background: Osteochondral lesions (OCL) of the talus are a significant cause of chronic ankle pain and functional impairment, typically following trauma. Despite advancements in diagnostic imaging and surgical interventions, long-term outcomes vary, and no gold standard treatment has been established. Methods: This retrospective study evaluated the outcomes of n=64 patients undergoing OCL-related surgery. Inclusion criteria: an OCL of the talus, patients without OCL, with osteoarthritis, or infection were excluded. The cohort was categorized primarily based on the stage of OCL and the surgical technique used: bone marrow stimulation by retrograde or anterograde drilling and microfracturing, transplantation of autologous cancellous bone, and acellular cartilage replacement and other procedures. Postoperative outcomes were assessed using the visual analog scale (VAS), the American Orthopaedic Foot & Ankle Society (AOFAS) score, and the Foot and Ankle Outcome Score (FAOS). Statistical significance was determined using χ2 tests, with P <.05 considered significant. Results: A total of 97 operations were performed on 64 patients. Fifty-six percent of patients reported complete resolution of symptoms, 25% experienced partial improvement, and 19% showed no improvement. Patients aged ≤30 years had a higher success rate (62.5%) compared with older patients (45.8%, P = .227). Success rates were significantly better for patients with stage II and III lesions (50% and 59%, respectively) than for those with stage IV lesions (P = .043). Material substitution had a success rate of 44.4%, bone marrow stimulation 37.8%, and other procedures 18.8%. Conclusion: Surgical techniques for treating OCL of the talus provide moderate success, but a significant proportion of patients, especially those with advanced lesions, remain symptomatic.
Keywords: ddc:610